Innowacyjność polskich przedsiębiorstw na tle Unii Europejskiej - Seredocha, Izabela (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
The ability of taking advantage of knowledge and information to create the innovation is a crucial factor in the success of any enterprise in the 21st century. The innovation of the Polish economy is unfortunately very weak because of relatively small contribution of companies, for instance, research institutions in creating new products and technologies. Moreover, not many Polish patents and know-how solutions are used abroad. Hopefully, the Polish entrepreneurs are conscious of importance of innovation for market position of their companies. But, on the other hand, they expect effective instruments from the Polish government supporting the implementation of the new solutions. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1191, s. 588-601